PENGUATAN BILINGUAL LEARNING ECOSYSTEM DALAM PENDIDIKAN KEWIRAUSAHAAN BAGI SISWA SMK DI MENTAWAI - Rosita, Nur; Solusia, Carbiriena; Sari, Astri Yuza (Jurnal Abdi Insani, 2025)
Vocational high schools graduates in Mentawai are expected to have career readiness not only as a job seeker, but also as a job creator due to the lack of job opportunities. This demand changes vocational high school curriculum to be as practical as possible in promoting various entrepreneurship programs to stimulate the entrepreneurial spirit added by English language skills. This issue is has become the initial background in conducting this community service activity. The purpose of this community service is to strengthen activities experienced by vocational high schools in SMKN 1 Kepulauan Mentawai in implementing Bilingual Learning Ecosystem on Entrepreneurship Education. Workshops and training activities are given to the students. The participants are 30 students vocational high schools in Mentawai. They were given a training to apply their English skill in Bilingual Learning Ecosystem. The result shows the willingness of the students to embody themselves in this Bilingual setting to sharpen their English skills. Therefore, concrete steps are needed to be done consciously. There should be continue assistances or trainings to strengthen entrepreneurial competencies and English language skills in business context for the students.